Maternal Cardiovascular Disease 3 Decades After Preterm Birth: Longitudinal Cohort Study of Pregnancy Vascular Disorders. Issue 3 (March 2020) - Auger, Nathalie; Potter, Brian J.; He, Siyi; Healy-Profitós, Jessica; Schnitzer, Mireille E.; Paradis, Gilles
Abstract : Women who deliver preterm are at risk of cardiovascular disease, but the reason for the association is unclear. We determined whether vascular disorders during pregnancy explain the association between preterm delivery and future maternal cardiovascular disease. We analyzed a longitudinal cohort of 1 199 364 pregnant women with 19 186 983 person-years of follow-up in Quebec between 1989 and 2017. We calculated incidence rates of myocardial infarction, ischemic stroke, and other cardiovascular hospitalizations. We used multivariable Cox regression to estimate adjusted hazard ratios and 95% CIs for the association of very and moderate preterm delivery with maternal cardiovascular hospitalization. We determined the proportion of the association that was due to preeclampsia, acute cardiac events at delivery, antepartum/postpartum hemorrhage, and heart defects. The incidence of maternal cardiovascular hospitalization was greater for very (43.7 per 10 000 person-years) and moderate (39.4 per 10 000) preterm delivery compared with term delivery (26.2 per 10 000). Very preterm delivery was associated with 1.67× the risk of cardiovascular hospitalization (95% CI, 1.56–1.79), and moderate preterm delivery was associated with 1.51× the risk (95% CI, 1.46–1.56). Vascular disorders during pregnancy explained 26.2% of the association of very preterm delivery and 24.0% of the association of moderate preterm delivery, with cardiovascular hospitalization. Preeclampsia was the largest contributor to these proportions. We conclude that vascular disorders during pregnancy, especially preeclampsia, explain up to a quarter of the association between preterm delivery and future maternal cardiovascular hospitalization. Abstract : Supplemental Digital Content is available in the text.